Cooperation in an Overlapping Generations Experiment - Theo Offerman; Jan PottersHarry A.A. Verbon; Harry A.A. Verbon (Tinbergen Institute, 1999)
Recent theoretical work shows that folk theorems can be developed for infiniteoverlapping generations games. Cooperation in such games can be sustained as aNash equilibrium. Besides the efficient cooperative equilibrium there is alsothe inefficient non-cooperative equilibrium. This paper investigatesexperimentally whether cooperation actually occurs in a simple overlappinggenerations game. Subjects both play the game and formulate full strategies. Inour base-line treatment subjects fail to exploit the intertemporal structure ofthe game. When we provide subjects with a recommendation to play a (subgameperfect) grim trigger strategy, a substantial part of the population developstrigger-like strategies. However, a remaining group of unconditional defectorsprevents the cooperative outcome to evolve.
Keywords: C72; C92; D90; 330; overlapping generations; cooperation; trigger strategies; experiments; Overlapping Generations; Kooperatives Spiel; Test; Theorie